THE STRATEGIES OF POSITIVE AND NEGATIVE POLITENESS REFLECTED IN “THE LAST SONG” NOVEL BY NICHOLAS SPARKS - Ambalegin Ambalegin; Meliana Sijabat (eScience Humanity Journal, 2020)
This research discussed  the positive and negative politeness strategies in The Last Song novel by Nicholas Sparks (2009). The data were the utterances in The Last Song novel. This research was mainly aimed to find out the strategies of positive and negative politeness. The theory applied in this research was taken from the book entitled “Politeness Some Universals in Language Usage” proposed by Penelope Brown and Stephen C Levinson (1987). This research was the descriptive qualitative research. Method of collecting the data used observational method by using non-participatory technique. In analyzing the data, the researcher used the pragmatic identity method. The research result showed that the characters in The Last Song novel applied all the strategies of positive politeness and negative politeness except the eighth strategy of negative politeness; state the face threatening act because The Last Song novel was the romantic novel and there was no regulation, obligation, social rule from the country.